?CAFFEINE INJECTION IN THE DARK PHASE PROLONGS THE NOCTURNAL RISE IN SEROTONIN N-ACETYLTRANSFERASEACTIVITY AND MELATONIN CONTENT IN THE PINEAL GLAND OF MALE RATS (Biological Sciences - PJSIR, 1999)
Caffeine, an important member of methylxanthines, induced aprolonged nocturnal rise in pineal melatonin content and an increase in its rate-limiting enzyme serotonin N-acetyltransferase (NAT) activity. The highest levels were reached five hours after subcutaneous caffeine injection to male rats in the dark phase, where the NAT activity increased from 920±70 pM pineallh' in the control group to 1190±120 pM pineal+b' (p